2022
DOI: 10.1016/j.vaccine.2021.11.061
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine uptake, effectiveness, and waning in 82,959 health care workers: A national prospective cohort study in Wales

Abstract: Background While population estimates suggest high vaccine effectiveness against SARS-CoV-2 infection, the protection for health care workers, who are at higher risk of SARS-CoV-2 exposure, is less understood. Methods We conducted a national cohort study of health care workers in Wales (UK) from 7 December 2020 to 30 September 2021. We examined uptake of any COVID-19 vaccine, and the effectiveness of BNT162b2 mRNA (Pfizer-BioNTech) against polymerase chain reaction (PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 24 publications
5
32
1
Order By: Relevance
“…We assessed the full texts of 36 articles, and we excluded 11 applying our inclusion and exclusion criteria. Finally, we included 25 studies in our systematic review and meta-analysis [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. The flow diagram according to PRISMA guidelines is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed the full texts of 36 articles, and we excluded 11 applying our inclusion and exclusion criteria. Finally, we included 25 studies in our systematic review and meta-analysis [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. The flow diagram according to PRISMA guidelines is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Main characteristics of the studies included in our review are presented in Table S1 . We found 25 studies including 491,624 vaccinated HCWs, while the full sample included 555,561 HCWs, ranging from 172 to 356,053 [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. The mean percentage of females was 67.3% (standard deviation = 19.9), and the mean age of the full sample was 39.2 years (standard deviation = 6.2).…”
Section: Resultsmentioning
confidence: 99%
“…There have been recent observational studies which have shown effectiveness similar to the randomised clinical trials (RCTs) across the globe, both test negative and cohort, [5][6][7][8][9][10][11][12] followed by studies across different patient populations, variants and number of doses. [13][14][15][16][17] Nevertheless, the challenges associated with the use of observational data such as incomplete data capture, outcome misclassification and appropriate comparator sampling can undermine the results of the studies if such biases are not accounted for.…”
Section: Introductionmentioning
confidence: 99%
“…When using the survival curve from our adjusted Weibull model for the complete dose, the protective efficacy of the vaccines by day 140 has been reduced to 38% and 71% respectively. Also Bedston et al (2022) estimates a VE of 86% by day 14 and of 53% by day 154 for PF vaccine after second dose, whereas our survival model for complete dose PF vaccine for those days is 99% and 66% respectively.…”
Section: Discussionmentioning
confidence: 87%
“…Tartof et al (2021) argues that a reduction in vaccine effectiveness against SARS-CoV-2 infections over time is more likely to be due to waning immunity rather than the delta variant escaping vaccine protection. Several studies suggest a significant waning of VE from 90 days after the second dose (Kurita et al, 2022; Andrews et al, 2022; Bedston et al, 2022; Ferdinands et al, 2022; Goldberg et al, 2021).…”
Section: Introductionmentioning
confidence: 99%